Harnessing GenAI to support vocabulary development in international students - Hunt, Rachel; Morgan, Leigh (Journal of Academic Language and Learning, 2026)
This practice-based project explored how international students at a pathway college could interact with Generative AI (GenAI) to develop academic vocabulary in a personalised and engaging way. The initiative aimed to develop vocabulary while promoting critical engagement with GenAI, preparing the students to use it ethically and effectively in both academic and professional contexts. Students used structured prompts which were designed to encourage deeper interaction beyond dictionary-style use and maintained individual vocabulary records to enable further development. Observations suggest that guided interaction with GenAI can support both language development and digital literacy.